Underdeveloped development cooperation. Lithuanian case - Ivinskienė, Giedrė (Politologija, 2023)
This article strives to reveal the reasons hindering smooth implementation of Lithuania’s development cooperation policy. Although Lithuania is less than 8 years away from the target of official development assistance at least 0.33% of Gross National Income (GNI) per year, it is currently contributing only about one-third of this amount, which naturally raises the question “Why?”. Theoretical framework of the motivations behind development cooperation enforcement, specifically, Europeanisation theory, is chosen to support the research. Bearing in mind the scarcity of the academic body of work for this topic, the main instrument, questionnaire for the in-depth interviews with the main decision makers of Lithuania’s development cooperation was created. 17 semi-structured interviews with experts from various backgrounds provided the valuable material for this analysis and helped to provide possible answers to the matter in question.
Keywords: Lithuanian development cooperation; foreign aid; official development assistance; ODA; Europeanisation; donor country